Membrane potentials and resistances of giant mitochondria. Metabolic dependence and the effects of valinomycin (The Rockefeller University Press, 1978)
The membrane potentials and resistances of giant mitochondria from mice fed cuprizone have been studied. They were found to correspond approx. 10-20 mV, positive inside, and 2 M omega, respectively. These properties were found to be independent of the metabolic state. The microelectrodes were in the inner mitochondrial space since (a) the potentials in the presence of valinomycin depended on the K+ concentration of the medium and magnitude of the K+ diffusion potentials was consistent with the presence of a high internal concentration of K+, (b) almost identical results were obtained with mitochondria from which the external membrane had been removed and the cristae were evaginated, and (c) punch-through experiments, in which the microelectrodes were advanced until they emerged through the other side of the mitochondria, showed an identical membrane potential both in the presence and in the absence of valinomycin. The potentials were stable under a variety of conditions and showed no sign of decay of membrane leakiness. Detailed evidence that the impaled mitochondria are metabolically viable will be presented in a separate publication.